2019
DOI: 10.1371/journal.pone.0221477
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M reduces atherosclerosis development in APOE*3Leiden.CETP mice and is associated with increased survival probability in humans

Abstract: Objective Previous studies indicate a role for Oncostatin M (OSM) in atherosclerosis and other chronic inflammatory diseases for which inhibitory antibodies are in development. However, to date no intervention studies with OSM have been performed, and its relation to coronary heart disease (CHD) has not been studied. Approach and results Gene expression analysis on human normal arteries (n = 10) and late stage/advanced carotid atherosclerotic arteries (n = 127) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
1
7
0
1
Order By: Relevance
“…Another possibility is that there is not only a decrease of OSMR expression on the arterial wall, but also a decrease in circulating OSMR levels, which can also bind to OSM and acts as a neutralizer (54), also resulting in no net difference in OSM signaling. Moreover, this study cannot make a distinction between the timing and the duration of OSM signaling, which may differentially affect atherosclerosis development as previous studies have shown that OSM, like IL-6, can act differently in the acute phase than in the chronic phase (8,9,55,56). Finally, we focused on only three genes (OSM, OSMR and LIFR), while atherosclerosis is a multifactorial disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another possibility is that there is not only a decrease of OSMR expression on the arterial wall, but also a decrease in circulating OSMR levels, which can also bind to OSM and acts as a neutralizer (54), also resulting in no net difference in OSM signaling. Moreover, this study cannot make a distinction between the timing and the duration of OSM signaling, which may differentially affect atherosclerosis development as previous studies have shown that OSM, like IL-6, can act differently in the acute phase than in the chronic phase (8,9,55,56). Finally, we focused on only three genes (OSM, OSMR and LIFR), while atherosclerosis is a multifactorial disease.…”
Section: Discussionmentioning
confidence: 95%
“…These observations are in line with our previous work, in which we showed that simultaneous signaling of OSM through OSMR and leukemia inhibitory factor receptor (LIFR), induces activation in human endothelial cells, suggestive of a role in atherosclerosis development (8). In contrast, chronic OSM administration to APOE * 3Leiden.CETP mice reduces the atherosclerotic lesion size and severity, and high circulating OSM levels correlate with increased post-incident coronary heart disease survival probability in humans (9).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, OSM has also been detected in atherosclerotic lesions of the human aorta and ApoE-deficient mice [92]. However, a recent study showed that the development of atherosclerosis was reduced on chronic administration of OSM, and high OSM levels coincided with an increased post-incident coronary heart disease survival probability in the AGES-Reykjavik study [93], indicating the complexity of correlation studies.…”
Section: The Osm/osmr/gp130 Axis and Early Cardiovascular Studiesmentioning
confidence: 99%
“…Another possibility is that there is not only a decrease of OSMR expression on the arterial wall, but also a decrease in circulating OSMR levels, which can also bind to OSM and acts as a neutralizer(54), also resulting in no net difference in OSM signaling. Moreover, this study cannot make a distinction between the timing and the duration of OSM signaling, which may differentially affect atherosclerosis development as previous studies have shown that OSM, like IL-6, can act differently in the acute phase than in the chronic phase(8,9,55,56). Finally, we focused on only three genes ( OSM, OSMR and LIFR ), while atherosclerosis is a multifactorial disease.…”
Section: Discussionmentioning
confidence: 90%
“…These observations are in line with our previous work, in which we showed that simultaneous signaling of OSM through OSMR and leukemia inhibitory factor receptor (LIFR), induces activation in human endothelial cells, suggestive of a role in atherosclerosis development(8). In contrast, chronic OSM administration to APOE*3Leiden.CETP mice reduces the atherosclerotic lesion size and severity, and high circulating OSM levels correlate with increased post-incident coronary heart disease survival probability in humans(9).…”
Section: Introductionmentioning
confidence: 99%